Battery plug-in electric vehicle part 2 : design, development, fabrication of transition structures and mounting of aluminium outer shell - Pang, Jun Wei (2018)
Global warming has been a growing issue over the past few years which not only affects our health, but also the environment and ecosystem. One of the main causes of global warming is the emission of greenhouse gas, especially the emission of carbon into the atmosphere. Therefore, it is important for us to constantly search for solutions to reduce the amount of carbon emission. One of the way is to introduce a Battery Electric Vehicle (BEV), an electric vehicle that utilises chemical energy that is stored in rechargeable battery packs, instead of using internal combustion engines like conventional vehicles. Nanyang Venture 7 is a BEV aimed to explore the concept of BEV as a solution for demand of a cleaner energy in the transport sector. The author is part of a group of final year students undertaking this ongoing project which was initiated at 2011. The objective of this final year project is to design a method for the marriage of aluminium outer shell to the chassis. The aluminium outer shell is soft and flimsy, hence it is necessary to design and fabricate a transition structure to mount the outer shell on and also provide additional strength for the outer shell. Calculations were done to ensure the structural integrity of the transition structure, where the final design of the transition structure was fabricated and assembled in-house through cutting, grinding and welding processes. Lastly the aluminium outer shell was mounted onto the transition structure, hence completing the marriage of the outer shell to the chassis. This report serves to document the detail of the author’s work in this final year project.